Lorentz Invariance Violation and Modified Hawking Fermions Tunneling Radiation - Shu-Zheng Yang; Kai Lin; Jin Li; Qing-Quan Jiang (Advances in High Energy Physics)
Recently the modified Dirac equation with Lorentz invariance violation has been proposed, which would be helpful to resolve some issues in quantum gravity theory and high energy physics. In this paper, the modified Dirac equation has been generalized in curved spacetime, and then fermion tunneling of black holes is researched under this correctional Dirac field theory. We also use semiclassical approximation method to get correctional Hamilton-Jacobi equation, so that the correctional Hawking temperature and correctional black hole’s entropy are derived.